Material and Optical Properties of Fluorescent Carbon Quantum Dots Fabricated from Lemon Juice via Hydrothermal Reaction - Meiqin He; Jin Zhang; Hai Wang; Yanrong Kong; Yiming Xiao; Wen Xu (Nanoscale Research Letters, 2018)
Abstract The water-soluble fluorescent carbon quantum dots (CQDs) are synthesized by utilizing lemon juice as carbon resource via a simple hydrothermal reaction. The obtained CQDs are with an average size of 3.1 nm. They reveal uniform morphology and well-crystalline and can generate bright blue-green light emission under UV or blue light irradiation. We find that the fluorescence from these CQDs is mainly induced by the presence of oxygen-containing groups on the surface and edge of the CQDs. Moreover, we demonstrate that the as-prepared CQDs can be applied to imaging plant cells. This study is related to the fabrication, investigation, and application of newly developed carbon nanostructures.